Helicobacter Pylori Infection And Gastric Cancer: Is It Our National Problem? - Rahman, M Mizanur; Alam, Shahjadul; Iqbal, Abu Mohammad Khaled; Hossain, Md Monoar; Sarker, Abu Mohammad Kawser; Islam, Monjurul (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Gastric cancer is a leading cause of cancer death worldwide. In Bangladesh it ranks a leading position among the cancers patients. A large body of evidence supports a causal role of Helicobacter pylori in the majority of gastric malignancies. Scientists throughout the world explored and reached to the understanding about the pathogenesis of their relationship, but much remains to be learned. Moreover, because of the high prevalence of infection, the lack of definitive trials, and the challenges of H. pylori treatment, there remains a debate regarding the consensus on the role of routine screening and treatment of this infection to prevent cancer. This article reviews the current knowledge on H. pylori and its role for gastric cancer, present status of Bangladesh and a recommendation for reduction of the infectivity among the common population. J Bangladesh Coll Phys Surg 2018; 36(2): 70-76